Enhancing Protein Fold Prediction Accuracy Using New Physicochemical-Based Features And Fusion Of Heterogeneous Classifiers - Dehzangi, Abdollah (2010)
One of the most challenging research areas in the bioinformatics is to predict the tertiary structure of a protein from its amino sequence. Difficulties of this task, such lack of knowledge about the protein structural stability or how the amino acids interact with each other along the amino acid sequence of a protein have made this an open search issue for the bioinformatics and the molecular biology.